الكفاءة المهنية للأستاذ الجامعي ومتطلبات تطويرها من وجهة نظر طلبة كليات التربية جامعة الزاوية - العموري, ناجية (Sharwes Scientific Journal, 2025)
The study was  aimed to identify the professional competencies and the requirements for their development available to the university professor in the faculties of education at the University of Al-Zawiya.  paragraphs, validity and reliability were verified, and then distributed over the research sample consisting of (182) female students in the faculty of education in Al-Zawiya, and the results showed the level of requirements for professional competencies that must be met by the university professor, which came at an average degree in all fields. The study also showed that there were no statistically significant differences among the sample members according to the kind of specialization (scientific - literary). Among the sample members, there are statistically significant differences between the sample members according to the educational level variable (first-eighth) in favor of the eighth level.